Increasing the amount of listeners of Pro 2 Radio Republik Indonesia (RRI) - Laksono Nainggolan, Guntur Agung; Setyabudi, S.Sos, MM, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
RRI is the only state radio network of Indonesia which means their broadcast acticvity is mainly for country importance. RRI as a independent, neutral and non-commercial public broadcast is obligate to provides information, education, good entertainment, social control, and also maintain positive image of indonesia in international..Pro 2 RRI Semarang broadcasts on FM 95,3 Mhz and has variety of education and entertainment programs start from 05.00 am until 12 pm WIB. PRO 2 RRI have developed some programs that based on life style. So they made a special channel that focus on young listeners that through this channel, they not only can speak their aspirations about anything but also share informations that relate to their age and their problems. The result from our field work shows that through some programs that we chose, we succeed to increase the amount of listeners of PRO 2 RRI semarang. At start, the listeners of Pro 2 RRI Semarang only reached 240 listeners per month. We increased it to 732 listeners per month during the execution of our field work. Success factor in our field work at PRO 2 RRI Semarang program is an combination of proper buzzing, good materials and quiz with prizes . Production Manager responsible to all the activities in the execution of the event and also responsible in the process of creative design in the execution of event.